The Rise of Micro-Da’i: Authority, Authenticity, and Monetization in Short-Form Islamic Content - Juni yanti; Rasman, Rasman; Mukhlizar, Mukhlizar; Desi Firmasari; N. Baskautshar (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study critically examines the psychometric properties of measurement instruments for key constructs in digital Islamic communication research, focusing on micro-dai phenomena. The analysis reveals fundamental methodological flaws, with Cronbach’s α (-0.072 to 0.090) and validity metrics (0.108–0.127) failing to meet acceptable thresholds. Discriminant validity assessment through Fornell-Larcker criterion demonstrated systematic measurement invalidity, while anomalous negative correlations between authenticity and donation behavior (-0.305) challenge theoretical assumptions. The findings necessitate reconceptualization of digital religious authority, authenticity, and audience engagement constructs, emphasizing context-sensitive instrumentation. This research provides crucial methodological insights for future studies in digital religion, highlighting the imperative for interdisciplinary approaches integrating communication theory, psychometrics, and digital culture studies to advance the field’s methodological rigor.